A relação entre as representações sociais de professores dos anos inicias sobre a Matemática escolar e as práticas pedagógicas adotadas em sala de aula - Alves, Maria de Lourdes carneiro (2025)
Mathematics has historically been a subject that evokes insecurity in many educators, especially due to the weakness of initial training in this area. This difficulty directly impacts pedagogical practices in the early years of schooling, making it necessary to understand how these teachers represent school mathematics. The objective of this study was to analyze the social representations constructed by teachers in the early years of schooling about mathematics and to identify how these conceptions influence their classroom practices. The research is characterized as qualitative, carried out in a municipal public school, with the participation of five teachers from the 1st to the 5th grade of elementary school. Data production occurred through semi-structured interviews, which were recorded and transcribed in full, conducted individually on different days, according to the availability of each participant. To support the analysis, we used Bardin's content analysis, aiming to systematize the scientific investigation method to interpret messages and meanings present in the accounts. The qualitative analysis was developed in three main stages: First stage – Exploration of the material: in this stage, the interview responses were analyzed, highlighting the excerpts considered relevant to the research objectives; In the second stage – Coding, in this phase, a line-by-line analysis was carried out, assigning codes to the excerpts or units of meaning identified as important for my study. Then, the initial codes were reorganized, related, and systematized into three main thematic categories. The initial list of codes was kept as a living document and updated throughout the process; third stage – Interpretation of the results: the coded and classified data were interpreted, where inferences were made in light of the theoretical frameworks of Serge Moscovici and Denise Jodelet, in the field of social representations, as well as authors in Mathematics Education such as Tardif, D’Ambrosio, and Nacarato. This stage sought to understand how teachers' representations manifest themselvesn in pedagogical practices. Selected excerpts from the interviews served as direct evidence for each category presented. The criteria for forming the two main categories considered the recurrence of codes, their relevance to the research objectives, and the theoretical support found in the literature on Social Representations and teaching practices. The analysis continued until theoretical saturation was reached, resulting in two main categories: a) the negative influences of the initial training of educators in relation to Mathematics, highlighting gaps in preparation for teaching this subject; b) the conceptions and practices of Mathematics developed by teachers in the classroom, revealing both the persistence of traditional methods and evidence of innovation when there is support from continuing education. It is concluded that understanding educators' social representations of Mathematics is essential to problematize crystallized practices and promote more meaningful, critical, and contextualized teaching, capable of bringing the subject closer to the reality of students.